PROTOTYPE SISTEM OTOMATISASI RUMAH BERBASIS IoT ( Internet of Things) - Adi Wibowo; Sigit Gunanto; Hartono Hartono (Jurnal Ilmiah Matrik, 2023)
Abstract : The progress in electronics is very significant. The concept of home automation systems has the potential to improve the living conditions of traditional homes. The aim is to provide convenience to the elderly and people with special needs. Our home automation system works effectively by providing clients with more personal happiness and comfort by using the automation system. Among the four popular wireless connections that will be implemented in this research is WIFI because the WIFI capabilities are more than enough to be implemented in the design. Also, most of the laptops/notebooks or Smartphones nowadays come with a built-in WIFI adapter. Indirectly will reduce the cost of this system. The research carried out has succeeded in making light and fan switching command displays using smartphones, tablet laptops can also use voice commands via Google Assistant. The results obtained are very responsive in receiving and responding to orders quickly and precisely.